Phosphatidylinositol- 3-kinase inhibitor induces chemosensitivity to a novel derivative of doxorubicin, AD198 chemotherapy in human bladder cancer cells in vitro. Issue 1 (December 2015) - Smolensky, Dmitriy; Rathore, Kusum; Cekanova, Maria
Abstract Background Doxorubicin (Dox) is widely used to treat progressed bladder cancer after transurethral resection. The use of Dox-chemotherapy has been limited due to induced drug resistance and cumulative cardiotoxic effects. N-benzyladriamycin-14-valerate (AD198), a novel derivative of Dox, has a potential to become a more effective treatment than Dox by overcoming drug resistance and cardio-toxicity as shown in the rodent model of lymphomain vivo . The purpose of this study was to compare the efficacy of Dox and AD198 and explore their mechanisms in inhibition on human bladder cancer cellsin vitro . Methods We evaluated the effects of Dox and AD198 on cell viability of human transitional cell carcinoma (TCC) cell lines T24 and UMUC3 by MTS assayin vitro . The effects of Dox and AD198 on cell apoptosis were determined by caspase 3/7 assay, generation of reactive oxygen species (ROS), and Western Blotting (WB) analysis. Results AD198 was more effective than Dox in inhibition of cell viability of T24 and UMUC3 cellsin vitro . Both Dox and AD198 significantly increased the generation of ROS and induced apoptosis in caspase-dependent and -independent manner in T24 and UMUC3 cells. AD 198 induced significantly higher production of ROS as compared to Dox in human TCC cells. Dox and AD198 activated the pro-apoptotic p38 MAPK pathway; however, on the other hand also increased phosphorylation of AKT, an anti-apoptotic signaling pathway, in T24 and UMUC3 cells. Combined treatment of PI3K inhibitor (LY294002) with Dox or AD198 inhibited cell viability of T24 and UMUC3 cells more effectively than any of drug treatments alone. Conclusions These data suggest that AD198 as novel derivative of Dox, could be a used as effective treatment for bladder cancer. Dox and AD198 induced PI3K/AKT signaling pathway that is a one of the indicators of pro-survival and possible drug-resistance mechanisms of chemotherapies in bladder cancer. Combined therapies of Dox or AD198 with inhibitors of PI3K/AKT signaling pathway might lead to more effective treatment outcome for patients diagnosed with bladder cancer based on ourin vitro experiments.